Effect of rice straw and its decomposed material on immobilization of cadmium in red soil by biochar - Trần Thị Biên, Thùy; Hu, Hong Qing (Tay Nguyen Journal of Sciences, 2023)
To effectively utilize agricultural wastes for soil cadmium immobilization has become hot topic of environmental science. This study examined the effect of rice straw (RS) and its decomposed product (DRS) on immobilization of Cd by rice straw biochar (BC). Results showed that, among all biochar treatments at the 3% application rate, the soil pH and organic matter content significantly increased with increasing the RS and DRS application rate from 0% to 15%. RS and DRS combined with BC in different rate made toxicity characteristics leaching test (TCLP) cadmium contents in soil reduced by the percentage of 6.2-25.1 and 6.2-31.7, respectively. For BCR sequential extraction procedure, the exchangeable-Cd and reducible-Cd fractions were transferred to oxidisable and residual-Cd fractions in both RS and DRS treatments when their combination with BC in various ratios. Overall, different rate of RS and DRS can promote immobilization effect of biochar on cadmium in red soil. The most effective treatment for immobilization of cadmium by biochar is 3% for raw rice straw and 0.6% for decomposed rice straw.